Recent advances in flame retardant epoxy systems containing non-reactive DOPO based phosphorus additives - Bifulco, Aurelio; Varganici, Cristian–Dragos; Rosu, Liliana; Mustata, Fanica; Rosu, Dan; Gaan, Sabyasachi (Polymer degradation and stability, 2022)
•Non-reactive DOPO-compounds show hybrid activity in gas and condensed phase.•Non-reactive DOPO-derivatives do not strongly affect the crosslinking in epoxy resin.•Sol-gel strategies allow for self-extinguishing systems cured with aliphatic agents.•DOPO functionalized nanostructures tailor the interphase and act as thermal insulator.•Self-extinguishing capability is mostly achieved via the use of aromatic hardeners. Epoxy resins are widely used in the manufacturing of fire safety products in the industry. 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) is a commercially available non-toxic reactive flame retardant and its incorporation improves the fire behavior of epoxy systems by releasing active phosphorus species to the gas phase. The reaction between DOPO and oxirane moieties negatively affects the glass transition temperature of epoxy-based composites and thus to overcome this drawback, it is usually modified to obtain non-reactive derivatives (i.e. mono- and multi DOPO derivatives). Besides, DOPO can also interact with the surface of silica- and carbon based nanostructures, leading to hybrid DOPO additives (“hybrid” term is referred to the organic-inorganic structure of such derivatives, which do not react directly with the polymer matrix). Non-reactive DOPO derivatives allow effective hybrid flame retardant mechanism and, in some hybrid –DOPO derivatives, good mechanical performances for the resin can be realized. This review focuses primarily on the technological advances in the last ten years (2011 onwards) on non-reactive DOPO derivatives for epoxy systems. Though DOPO is quite a common flame retardant additive in the polymer industry, for commercial exploitation of its derivatives, there is a need to develop economical alternative synthesis methodologies.